Blockchain integration into the university education process: a systematic review of application, justification, and impact - Irma Aybar-Bellido; Maritza Arones; José Antonio Arévalo-Tuesta; Willy Adauto-Medina; Hernán Ochoa-Carbajal (International Journal of Evaluation and Research in Education (IJERE), 2026)
As universities seek to integrate disruptive technologies to optimize their academic and administrative processes, a gap persists in the adoption of Blockchain as a strategic tool. Many higher education institutions still lack its implementation, limiting its potential to improve traceability, transparency, security, and the automation of different processes. Given this scenario, this study aims to identify the areas of application, the justifications for its use, and the impact of Blockchain when integrated into the university educational process. To this end, a systematic literature review was conducted with a mixed approach and an exploratory-descriptive scope, following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guideline, in the Scopus, ERIC, and SAGE databases. Of 3,469 manuscripts identified, 42 met the inclusion and exclusion criteria. The results show a predominance of applications focused on the validation and monitoring of academic achievements, with limited integration into pedagogical approaches such as active methodologies, adaptive learning, or competency-based learning. Based on a comparative analysis of trends, application areas, and thematic gaps, it is concluded that the expansion of Blockchain into educational models requires progressive implementation strategies, curricular integration, and teacher training, thereby generating more personalized, efficient, and transparent learning environments.